Answer:
3^16
Step-by-step explanation:
12^8 * 9^12
Rewrite 12 as 3*4 and 9 as 3*3
(3*4)^8 * (3*3)^12
We know that (ab)^c = a^c * b^c
3^8 4^8 3^12 3^12
We can write 4 as 2^2
3^8 2^2^8 3^12 3^12
We know a^b^c = a^(b*c)
3^8 2^(2*8) 3^12 3^12
3^8 2^(16) 3^12 3^12
We also know that a^b *a^c *a^d = a^(b+c+d)
2^(16) 3^8 3^12 3^12
2^(16) 3^(8+12+12)
2^16 3^(32)
But we need 6 ^16 so we will need a 3^16 3^32 = 3^16 * ^16 (16+16=32)
2^16 *3^16 *3^16
Remember a^b*c^b = (ac)^b
(2*3)^16 3^16
6^16 3^16
Answer: A and D
Step-by-step explanation:
Answer:
2, 4.5 and 8
Step-by-step explanation:
(1)
The mode is the number which occurs most often , then
mode = 2
(2)
The median is the middle value of the numbers arranged in ascending order. If there is no exact middle value then it is the average of the numbers either side of the middle.
1, 2, 2, 3, 4, 5, 6, 7, 8, 9
↑ middle
median =
=
= 4.5
(3)
The range is the difference between the largest and smallest values
range = 9 - 1 = 8
It's C they are just out of order for the years.
f(x)=35.5x+6
For each year your plug in the snow total for x and solve
2006 x=53 so 35.5(53)+6=1887.5
2007 x=42 so 35.5(42)+6=1497
2008 x=55 so 35.5(55)+6=1958.5
2009 x=63 so 35.5(63)+6=2242.5
2010 x=58 so 35.5(58)+6=2065
2011 x=47 so 35.5(47)+6=1674.5
Hope that helps.
8 x - 4 (5 - x) = -44
mutiply the bracket by -4
(-4)(5) = -20
(-4)(-x)= 4x
8x-20+4x= -44
8x+4x-20= -44 ( combine like terms )
12x-20= -44
move -20 to the other side
sign changes from -20 to +20
12x-20+20= -44+20
12x= -44+20
12x= -24
divide both sides by 12
12x/12= -24/12
Answer: x= -2